2013 13th IEEE International Conference on Nanotechnology (IEEE-NANO 2013) 2013
DOI: 10.1109/nano.2013.6721027
|View full text |Cite
|
Sign up to set email alerts
|

Nano sized silver for electronic packaging

Abstract: Production of modern microelectronic devices needs advanced materials and packaging technologies oriented towards the miniaturization and high reliability of the systems. Nano sized silver can be treated as such advanced material and it is used in modern packaging technologies, especially for flexible electronics. The paper presents information about the practical use of silver particles with the size from 4 nanometers in materials for electronic packaging technologies.The special ink containing nanosilver is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The previous studies [5] on material contained Ag nanoparticles with narrow size distribution from 3-10 nm in form of ink for ink-jet printed technology (ink AX JP-6n developed by Amepox Microelectronics LTD) showed that the low pressure or even pressure-free sintering process is possible. The experimental results on measurement of resistance change of ink-jet printed structures sintered in different temperatures showed that the sintering process time strongly depends on temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies [5] on material contained Ag nanoparticles with narrow size distribution from 3-10 nm in form of ink for ink-jet printed technology (ink AX JP-6n developed by Amepox Microelectronics LTD) showed that the low pressure or even pressure-free sintering process is possible. The experimental results on measurement of resistance change of ink-jet printed structures sintered in different temperatures showed that the sintering process time strongly depends on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In novel colloid developed by Amepox the silver nanoparticles are covered with different (polymer) coating and the mean size of particles is about 70nm. Even the size of Ag nanoparticles is one order of magnitude higher than in previous ink, the sintering process of such material would be carried out in lower temperature (150 °C) during 1h [5,[9][10][11] giving similar value of electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%